(untitled) (Baghdad Science Journal, 2015)
The aims of this study the infection with parasites Entamoeba histolytica and Giardia lamblia and prevalence rates and their relationship with gende , age group , the number of family members and source of drinking water among the patients at attending the Bint Al Huda and Al- Hussin Teaching hospital in Nassriyia city in Thi- Qar province , it was noticed that the percentage of parasitic infection at females was 38.55% and at males was 61.45% and the percentage of parasitic infection with Entamoeba histolytica 97% was higher than the percentage of parasitic infection with Giardia lamblia 3%,and the reduction of percentage of infection is associated with increasing of the number of family member ,the percentage of infection was 49% at the age group less than one year while it was 4% at the age group more than 15 year ,and the percentage of infection was increasing with number of family members .It was noticed that the higher percentage of infection was (45%) at families with members more than 15 person